INOVASI EKONOMI KREATIF MELALUI PELATIHAN PEMBUATAN SABUN CUCI PIRING DI PKK RT 06 KELURAHAN JAYA MUKTI KOTA DUMAI - Fitra, Fitra; Mesra, Trisna; Abdillah, Nuryasin; Melliana, Melliana; Azmi, Azmi; Hafrida, Lis; Simanullang, Sanco; Faisal, Rudi (Komunitas Manajemen Kompetitif, 2024)
The dish soap-making training conducted for the women of PKK RT 06 in Kelurahan Jaya Mukti, Kecamatan Dumai Timur, aimed to enhance their skills and knowledge in the creative economy sector. The activity involved 40 participants and included both theoretical and practical sessions, where participants were taught about ingredients, the soap-making process, and safety and hygiene techniques. The training results showed significant improvements in participants' knowledge and skills. Before the training, most participants lacked basic knowledge of dish soap-making. After the training, they were able to independently produce high-quality soap. This training also strengthened the camaraderie and cooperation among PKK members. However, participants faced challenges in sourcing raw materials. To address this, future training should focus on practical solutions such as providing information on affordable raw material sources and marketing strategies. The sustainability of this training is crucial, with government and stakeholder support needed to help participants develop their dish soap businesses sustainably. This training demonstrates that with the right methods and high motivation, the community can develop new skills beneficial for improving family economies.